1994
DOI: 10.4315/0362-028x-57.5.403
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of Vibrio parahaemolyticus and Vibrio vulnificus in Various Seafoods with Two Enrichment Broths

Abstract: This study compares recoveries of Vibrio parahaemolyticus and Vibrio vulnificus with salt-polymyxin B broth (SPB) and alkaline peptone water (APW) from samples of crab legs, oysters, shrimp, lobster and shark, which were inoculated at three levels (approximately 101 to 102, 102 to 103 and 104 to 105/g) with each of the pathogens. Six samples of each product were analyzed [3-tube most probable number (MPN)] with each broth. Inoculated samples of oysters and slurries of crab and lobster were also tested after co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Many species of Vibrio may be isolated with different solid media such us cellobiose polymyxin B colistin (CPC), blood agar flooded with oxidase reagent after incubation, or mannitol–maltose agar (Hagen et al. 1994; Donovan and van Netten 1995).…”
Section: Laboratory Detection Of Vibrio Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…Many species of Vibrio may be isolated with different solid media such us cellobiose polymyxin B colistin (CPC), blood agar flooded with oxidase reagent after incubation, or mannitol–maltose agar (Hagen et al. 1994; Donovan and van Netten 1995).…”
Section: Laboratory Detection Of Vibrio Sppmentioning
confidence: 99%
“…Many species of Vibrio may be isolated with different solid media such us cellobiose polymyxin B colistin (CPC), blood agar flooded with oxidase reagent after incubation, or mannitol-maltose agar (Hagen et al 1994;Donovan and van Netten 1995). The FDA procedure includes the evaluation of V. parahaemolyticus pathogenicity by detection of the Kanagawa phenomenon using Wagatsuma agar, containing high-salt blood to detect the haemolytic activity of V. parahaemolyticus thermostable direct haemolysin (TDH)-positive strains only.…”
Section: Laboratory Detection Of Vibrio Sppmentioning
confidence: 99%
“…To counteract for these phenomena, a plethora of alternative enrichment broths and plating media have been developed (Oliver, 1981; Oliver et al. , 1992; Hagen et al. , 1994; Azanza et al.…”
Section: Cultural Methodsmentioning
confidence: 99%
“…For example, Hara-Kudo et al (2001) observed that when seafood was evaluated for the presence of V. parahaemolyticus, colonies on TCBS agar were difficult to distinguish visually from other bacterial colonies because of the presence of a yellow pigment produced by sucrose fermenting bacteria. To counteract for these phenomena, a plethora of alternative enrichment broths and plating media have been developed (Oliver, 1981;Oliver et al, 1992;Hagen et al, 1994;Azanza et al, 1996;Høi et al, 1998a,b;Cerda´-Cue´llar et al, 2000;Alam et al, 2001). For example, CHROMagarÔ Vibrio is a differential medium that represents an alternative to TCBS.…”
Section: Cultural Detection and Enumerationmentioning
confidence: 99%
“…A proporção de cepas produtoras de gastrenterite varia de acordo com as condições geográ-ficas e sazonais, portanto a freqüência de isolamento é maior, nos meses de verão, quando podem ocorrer surtos ou casos esporádicos de gastrenterite, após consumo de água ou alimentos marinhos contaminados [8,9,12,15,23,30].…”
unclassified